Javanese wayang system of signs in batik logo and its role in creating visual brand identity - Pangestu , Melinia Enggal; Murtono, Taufik; Kurniawan, Rendya Adi (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
Batik was one of Indonesia's cultural heritages that had been recognized worldwide. Batik in Indonesia was diverse in terms of products and producing regions. One of the Batik-producing areas in Indonesia was Masaran in Sragen Regency. Batik producers in Kliwonan had their business names complete with logos as trademarks. One form of this was using names and images of wayang characters in trademarks, which had been done for a long time. This study analyzed four Batik company logos in Kliwonan Village, Masaran District, Sragen Regency, which were found using images of puppet figures, namely Janoko Kembar Batik, Sadewa Batik, Dewi Brotojoyo Batik, and Dewa Rama Batik. The research phase begins with data collection in the form of visual logos and literature related to the meaning of puppet figures. Data analysis is carried out by identifying the visual elements of the logo, including colors, illustrative images, typography, and layout as the first sign system (denotation). The denotational data is then read using a second sign system (connotation), which involves analyzing the characters of the puppet characters. The character of the puppet character that is understood is then discussed in a cultural context (myth). Roland Barthes' semiotic analysis is used to describe signs through first-order meaning (denotative), second-order meaning (connotative), and interpretation of meaning in cultural contexts (myth) The reading of the logo sign system was confirmed by interviews with the Batik entrepreneurs. The research results described the system of signs in denotation, connotation, and mythical meaning in the logos studied, which was in line with the application of visual elements and design principles. This research concluded that wayang could be used to discover self-identity for brand owners. The visual formation of brand identity in this study occurs through the selection of illustrations of images, colors, typography, and personal layout by brand owners. Illustrations of puppet characters are selected from the types of knights and princesses that give good character meaning. The selection of knight and princess characters can be a logo design model that uses puppet characters.